Gel nail polish as an alternative to traditional coverslip sealants: A quick solution to a sticky situation - Gabriela Kennedy; Daryan Chitsaz; Jeanne F. Madranges; Melissa Peştemalciyan; Abbas F. Sadikot; Timothy E. Kennedy (MethodsX, 2023)
A widespread protocol to seal coverslips on a microscope slide for histological analysis utilizes air-drying nail polish. Nail polish is applied to glue the coverslip in place and prevent the leakage of mounting media. Air drying takes time, typically overnight, and generates an unpleasant smell. Equally familiar is the waiting game, lightly touching the polish to check its dryness, while being careful not to disrupt the coverslip, often leaving sticky spots on one's fingertips. An advantageous solution to these drawbacks is to use gel nail polish, which rapidly hardens and dries by being cured under a LED/UV lamp. We show that UV-cured gel nail polish provides a rapid, stable, scentless, nontoxic, and cost-effective solution for coverslip sealing. Cured in 10 s, with no impact on fluorescent labels, gel polish hardens completely and the slide is ready to be imaged. Furthermore, we show that gel nail polish can be used to generate 3D ridges and structures to support coverslipping thicker samples. Gel nail polish is purposefully unscented, and the brands used in our study employ environmentally conscious, vegan, and cruelty-free ingredients. UV-cured gel nail polish is a cost-effective alternative that presents an easy, accessible, and inexpensive solution to traditional coverslip sealing methods. • Inexpensive method to rapidly seal coverslips onto a microscope slide to immediately image samples for Histological analyses. • Utilizes LED/UV light to cure gel nail polish in 10 s without bleaching fluorophores. • Can be used to generate 3D ridges and structures to support coverslipping thicker samples.